Efficient removal of heavy metal ions from the water of oil‐rich regions using layered metal‐phosphate incorporated activated carbon nanocomposite. (24th June 2020) - Esmaeili Bidhendi, Mehdi; Abedynia, Sara; Mirzaei, Seyed Saber; Gabris, Mohammad Ali; Rashidi Nodeh, Hamid; Sereshti, Hassan
Abstract: In this study, a metal‐phosphate layered/activated carbon (KMSP@AC) composed of potassium (K), manganese (Mn), tin (Sn) and phosphorous (P) was prepared by the solvothermal method. The proposed nanocomposite was used as an effective adsorbent to remove Cd(II), Co(II), Ni(II), Pb(II) and V(III) from water samples in oil‐rich areas prior to ICP‐OES analysis. The KMSP@AC was fully characterized using FTIR, SEM and EDX. Factors influencing the removal process (pH, adsorbent dosage, initial concentration and contact time) were studied and optimized. The experimental process was evaluated with kinetic and isotherm models. The adsorption isotherm investigation showed that the adsorption followed the monolayer Langmuir isotherm model with the maximum adsorption capacities of 25 mg/g (Cd 2+ ), 31 mg/g (Co 2+ ), 49 mg/g (Ni 3+ ), 91 mg/g (Pb 2+ ) and 141 mg/g (V 3+ ). The kinetic studies indicated that the pseudo‐second‐order model is well‐fitted to the process with an appropriate correlation coefficient ( R 2  > 0.99) at an equilibrium time of 120 min. The adsorption of metal ions on the surface of the adsorbent was mainly a physisorption process through electrostatic interactions.